Pathogenic and genomic characterisation of a rabbit sourced Pasteurella multocida serogroup F isolate s4 - Jinxiang Wang; Shikun Sun; Yanfeng Chen; Dongjin Chen; Lei Sang; Xiping Xie (BMC Veterinary Research, 2022)
Abstract Background Pasteurella multocida is one of the most significant pathogens for a number of animals. In rabbits, the infection is generally associated with the P. multocida serogroups A and D, and the knowledge about the serogroup F is limited. In the present study, a P. multocida serogroup F isolate designated s4 was recovered from the lungs of rabbits died of respiratory disease in Fujian, in the southeast of China. The pathogenicity and genomic features of the s4 were then determined. Results The serotype and sequence type of s4 were F:L3 and ST12, respectively. The s4 was pathogenic for rabbits, but it was a low virulent strain comparing to the previously reported highly pathogenic P. multocida serogroup F strains J-4103, C21724H3km7, P-4218 and HN07. The whole genome of the s4 was then sequenced to understand the genomic basis for pathogenicity. Particularly, a large-sized fragment of approximate 275 kb in length was truncated from the chromosome to form a plasmid. Moreover, the in-frame deletion of natC and N-terminal redundance of gatF would resulted in the production of a mutant L3 outer core structure that was distinct from those of the other P. multocida strains belonging to the lipopolysaccharide genotype L3. We deduced that these features detected in the genome of s4 might impair the pathogenicity of the bacterium. Conclusions This study evaluated the pathogenicity and determined the genomic features of the rabbit sourced P. multocida serogroup F isolate s4, the observations and findings would helpful for the understanding of the pathogenicity variability and genetic diversity of P. multocida.